959 Undertaking Core Surgical Training Less Than Full Time: A Qualitative Study of Experiences. (4th May 2021) - Kelly, M; Chiang, Y; Corte-Real Houlihan, M; Haylock-Vize, P; Larsen, C; Lilis, L; Maki, S; Milt, K M; Shee, J; Spoone, L; Warre, M
Abstract: Introduction: The Royal College of Surgeons identifies Less Than Full Time Training (LTFT) as a key factor in attracting excellent candidates at Core level. Previous evaluations of LTFT have, however, focused on ST3 and beyond. This study focuses on Core Surgical Training (CST), to determine how well it is delivering for LTFT trainees. Method: Participants undertaking any part of CST LTFT were eligible. An electronic, self-administered questionnaire was accessed by participants. Results: There were 11 participants. The majority (55%) rated the information available, which often related to more senior trainees, as poor. A third reported it 'very difficult' to arrange a LTFT training post. A significant proportion felt their access to operative experience was decreased and 45% reported feeling less confident. Positive aspects were improved work-life balance and being able to maintain a surgical career with a family. Suggestions for improvements included normalising LTFT in surgery to reduce stigma, having dedicated LTFT TPDs, clear pathways, and longer rotations. Conclusions: Training LTFT offers many benefits – not least, increasing workforce diversity. However, for many, training LTFT at Core level produces additional stress, work and stigma. If the surgical community is serious about maintaining an excellent, diverse workforce, these issues should be tackled sooner rather than later.